Key drivers of life-cycle environmental and cost assessment of windows for different European climate zones - Saadatian, Shiva (2022)
Windows are challenging building components regarding their life-cycle performance, which are influenced by parameters that often present trade-offs between environmental impacts and costs. To support the selection of windows with the lowest environmental and cost impacts in an early-design stage of buildings, it is essential to identify the key drivers to reduce the time and effort of a life-cycle assessment (LCA). A sensitivity analysis was performed to identify and rank the parameters that contribute the most to the variability in life-cycle global warming and cost of windows for three European climates. A set of alternative window configurations combining window- and operation-related parameters was investigated. The results showed that window-related parameters are more influential than operation-related parameters. The highest influential parameter on global warming and cost was window-to-wall ratio, for all orientations and locations. Other influential parameters depend on the location: for warmer climates, smaller windows are recommended or bigger windows with low solar factors; for colder climates, bigger windows are recommended or small windows with high solar factors. Thermal transmittance value has a large influence on smaller windows in warmer climates and on bigger windows in colder climates. The identification of key influential parameters and their ranking is important to support the environmental and cost LCA at an early-design stage of buildings, when window selection is flexible and more informed decisions can be made to promote lower impacts and costs.